Relação das práticas de governança cooperativa com o desempenho das cooperativas de crédito no Brasil - Souto, Lauana da Conceição Cabral (2018)
The research investigated the relatioship between credit cooperatives governance guidelines and their financial performance. In this regard, the theoretical framework was based on corporative governance, Agency Theory adapted to cooperatives realities following the Best Practices of Governance to Credit Cooperatives. Specifically, in the dimensions of "Structure, Administration and Management Council" and, the Resolution 4.434/2015 of Brazilian Central Bank, which deal with the implementation of mechanisms of governance in credit cooperatives. The methodology is stated as descriptive and explanatory using descriptive statistics, cluster analysis, correspondence analysis, e Pearson Correlation. The sample is composed of 39 cooperatives surveyed online using Google Docs forms, and financial data of the balancesheet provided by Central Bank following the framework of Bressan (2010). The results suggest the Credit Cooperatives studied present a higher level of Central Bank guidelines implemented. Just the index that presents the relationship between operational revenues and governance index (IGCC) was negative. Therefore, the main contribution of this research regards to the fact cooperative administration are engaged in good practices in order to generate value to their members.